The West Coast as a Literary Capital: Independent Publishers as a Contumacious Canon of Underground Poetry - William Mohr (IdeAs)
Robert Darnton’s communication circuit most often results in a default privileging of authors, readers, printers, and critics. This paper will examine a sequence of literary projects by West Coast publishers of poetry between 1955 and 1985 that was meant to challenge the hegemony of East Coast publishers. Moreover, these independent publishers aspired to establish a West Coast canon of poets as a separate and distinct roster worthy of the region being recognized as a contemporary literary capital. In often conflating the roles of publisher (as “first reader”), editor, printer, book distributor, and critic, these independent presses on the West Coast generated a critical mass of poets aligned with heterogeneous communities. In the midst of the turbulence of postmodernism, as it ever intensified, these poets made use of their juxtaposition with each other through their identification with independent publishers to reinforce their poetics in a variety of schools and movements. In particular, this paper presents detailed lists of poets in which the primary axis is their publisher(s).